(untitled) (The Research of Medical Science Review, 2024)
To compare the outcomes of pneumatic and laser lithotripsy among patients with proximal ureteric stones. The prospective randomized control trial study was conducted in the Department of Urology, Sindh Institute of Urology & Transplantation (SIUT), Karachi. Patients between the age group 18-70 years old, either gender with a size 8-15 mm proximal ureteric stones were included through non-probability consecutive sampling, which were assigned to two equal groups of pneumatic lithotripsy and laser lithotripsy. Patients were subjected to a CT KUB scan to confirm the presence and size of ureteric stones. The empirical antibiotics were given both just before the procedure (preoperative) and at least 5 days post-procedure or more. The follow-up assessment was noted after 4 weeks, to assess the outcomes like stone clearance, migration, and need of any secondary intervention. The SPSS version 26.0 was used to analyze the collected data with 95% C. I and 5% level of significance. The mean ± standard deviation of age in the pneumatic group was 40.83 ± 14.09 and laser group was 40.40 ± 14.28 years. In the pneumatic group, 48.6% were male and 62.9% were female while in the laser group, 51.4 were males and 37.1% were females. Stone clearance was significantly higher in the laser group (74.3%) compared to the pneumatic group (48.6%), stone migration was more common in the pneumatic group (42.9%) compared to the laser group (14.3%), and the need for secondary intervention was higher in the pneumatic group (51.4%) than in the laser group (28.6%). The results of this study indicate that laser lithotripsy was more efficacious in the treatment of proximal ureteric stones compared to pneumatic lithotripsy with higher stone clearance, and lower rates of migration. Although more time and expense are requiredfor laser lithotripsy, its low requirement of secondary interventions makes it the preferable option. For these particularly high-risk cases, laser lithotripsy should be selected to minimize stone migration and promote clearance. Larger studies are warranted to validate these results and to inform treatment algorithms.Laser Lithotripsy, Management, Pneumatic Lithotripsy, Proximal Ureteric Stone